2007
DOI: 10.1038/nrn2040
|View full text |Cite
|
Sign up to set email alerts
|

HIV and antiretroviral therapy in the brain: neuronal injury and repair

Abstract: Approximately 40 million people worldwide are infected with human immunodeficiency virus (HIV). Despite HIV's known propensity to infect the CNS and cause neurological disease, HIV neurocognitive disorders remain under-recognized. Although combination antiretroviral therapy has improved the health of millions of those living with HIV, the penetration into the CNS of many such therapies is limited, and patients' quality of life continues to be diminished by milder, residual neurocognitive impairment. Synaptoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
396
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(410 citation statements)
references
References 144 publications
10
396
1
3
Order By: Relevance
“…For example, it has been shown that dephosphorylation and inhibition of the IRBIT released with inositol 1,4,5-trisphosphate leads to Ca 2ϩ release from the ER and causes aberrant neuronal regulation (49), whereas the stress-associated endoplasmic reticulum protein 1 (SERP1) has been shown to stabilize ER membrane proteins during stress (50) and protects unfolded target proteins against degradation during ER stress. Similarly, maintaining the proper axon diameter size by NEFM is essential for the conduction of nerve impulses (51). Furthermore, distribution of the mitochondria inside the axon is essential to control ATP levels and cell-to-cell communication.…”
Section: Identification Of Genes Regulated By Tat In Neurons-mentioning
confidence: 99%
“…For example, it has been shown that dephosphorylation and inhibition of the IRBIT released with inositol 1,4,5-trisphosphate leads to Ca 2ϩ release from the ER and causes aberrant neuronal regulation (49), whereas the stress-associated endoplasmic reticulum protein 1 (SERP1) has been shown to stabilize ER membrane proteins during stress (50) and protects unfolded target proteins against degradation during ER stress. Similarly, maintaining the proper axon diameter size by NEFM is essential for the conduction of nerve impulses (51). Furthermore, distribution of the mitochondria inside the axon is essential to control ATP levels and cell-to-cell communication.…”
Section: Identification Of Genes Regulated By Tat In Neurons-mentioning
confidence: 99%
“…For example, dephosphorylation and inhibition of the IP 3 R-binding protein (IRBIT) released with IP 3 leads to Ca 2ϩ release from the ER and causes aberrant neuronal regulation (32), while the stress-associated endoplasmic reticulum protein 1 (SERP1) has been shown to stabilize ER membrane proteins during stress (33) and protects unfolded target proteins against degradation during ER stress. Similarly, maintaining the proper axon diameter size is essential for the conduction of nerve impulses (34). Further, distribution of the mitochondria inside the axon is essential to control ATP levels and cell-to-cell communication.…”
Section: Detection Of Vpr In Neural Cells Inmentioning
confidence: 99%
“…injection (40 l) on days 0, 3, 7, 14, 21, and 28 (3 doses in the first week, followed by weekly dosing for another 3 weeks) over 4 weeks. Blood samples were collected on days 1,3,7,8,14,15,21,22,28, and 29. On day 35, half the mice in each group (n ϭ 5) were sacrificed and tissues and blood samples were collected.…”
Section: Chemicalsmentioning
confidence: 99%
“…ART has transformed HIV disease into a long-term manageable disorder (1,2). However, treatment failure and related drug resistance remain an issue with ART, which can contribute to suboptimal drug efficacy, variable pharmacokinetics, poor adherence to lifelong therapy, comorbid conditions, substance abuse, and inherent ART toxicities (3)(4)(5).…”
mentioning
confidence: 99%